2009
DOI: 10.1096/fj.09-140566
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ ‐independent positive molecular inotropy for failing rabbit and human cardiac muscle by α‐myosin motor gene transfer

Abstract: Current inotropic therapies used to increase cardiac contractility of the failing heart center on increasing the amount of calcium available for contraction, but their long-term use is associated with increased mortality due to fatal arrhythmias. Thus, there is a need to develop and explore novel inotropic therapies that can act via calcium-independent mechanisms. The purpose of this study was to determine whether fast alpha-myosin molecular motor gene transfer can confer calcium-independent positive inotropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
1
26
1
Order By: Relevance
“…For example, an adenovirus construct was used to transfect human MYH6 into myocytes to increase their contractility 105 . The dominant isoform in the human ventricle is MYH7, which is slower and generates less force, but more energy-efficient.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, an adenovirus construct was used to transfect human MYH6 into myocytes to increase their contractility 105 . The dominant isoform in the human ventricle is MYH7, which is slower and generates less force, but more energy-efficient.…”
Section: Future Directionsmentioning
confidence: 99%
“…Myocytes were isolated from PTIP + and PTIP -mice, and shortening assays and Fluo-4AM calcium transients were performed as previously described (37).…”
Section: Figurementioning
confidence: 99%
“…Although the reported decrease in ␣-MHC content in human failing hearts is relatively small (ϳ10% of total MHC), it may have a significant impact on ventricular mechanical function if ␣-MHC is regionally distributed as it is in hearts of other mammalian species (12,62). Several studies (25,26,34,62,67,70) have demonstrated that a relatively small decrease in ␣-MHC expression can have significant impact on in vitro and in vivo contractile performance. Our results cannot directly assess the effects of small decreases of ␣-MHC on global LV mechanical performance because our mechanical measurements were conducted on hypothyroid hearts that lack ventricular ␣-MHC and euthyroid hearts expressing ϳ80% ␣-MHC in the ventricles.…”
Section: Consequences Of Altered Mhc Expression On In Vivo Contractilmentioning
confidence: 99%